The relative frequency of paediatric oral and maxillofacial pathology in New Zealand: A 10‐year review of a national specialist centre. Issue 2 (14th November 2019) - Yu, Zhihan; Seo, Benedict; Hussaini, Haizal M.; Meldrum, Alison. M.; Rich, Alison. M.
Abstract: Background: There has been no previous report of the prevalence of paediatric oral and maxillofacial pathology in a New Zealand oral pathology diagnostic service. Aim: The aim of this study was to review cases of paediatric oral pathology to determine relative frequencies of oral lesions in this age group. Design: Paediatric oral pathology cases (≤15 years of age) received between 2007 and 2016 were retrieved from the electronic database of the Oral Pathology Centre, University of Otago. Data collected included diagnoses (categorised into 12 groups), age at diagnosis, and gender. The prevalence of each diagnosis was calculated in terms of percentage of all diagnoses made. Male‐to‐female ratio and mean age at diagnosis were also determined. Results: A total of 1139 paediatric cases were identified representing 5.2% of all cases. The most common diagnostic group was salivary gland pathology (25.4%), followed by dental (24.8%) pathology. The most prevalent lesion was mucocoele (23%), followed by dental follicle (14.1%). Malignancies were rare with only two cases identified. Conclusion: The findings provide an insight into the prevalence of paediatric oral pathology for clinicians. Mucocoele was the most common diagnosis made, suggesting a high prevalence of soft tissue injury as a main presenting concern warranting diagnosis and management through biopsy.